2019
DOI: 10.9740/mhc.2019.07.275
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of naloxone use in the outpatient setting

Abstract: Introduction Naloxone has become an important component of preventing deaths from opioid overdose. Although studies have confirmed its cost-effectiveness, naloxone is rarely prescribed proactively in case of accidental overdose. The perception still exists that a reversal agent may enable patients with opioid use disorder to continue abusing opioids without fear of death from overdose. This study was designed to determine the general public's knowledge of naloxone and their perceptions about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…Addiction stigmas extended to the overdose antidote naloxone (Narcan®), the ready availability of which was viewed by commenters within the misdirected attention and individual blame category as enabling persons with addiction by providing a “safety net” against the negative consequences of drug use. These comments echo findings from other studies highlighting beliefs among community members and health care workers that naloxone availability serves to enable or encourage opioid use (Gatewood et al, 2016; Smith et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…Addiction stigmas extended to the overdose antidote naloxone (Narcan®), the ready availability of which was viewed by commenters within the misdirected attention and individual blame category as enabling persons with addiction by providing a “safety net” against the negative consequences of drug use. These comments echo findings from other studies highlighting beliefs among community members and health care workers that naloxone availability serves to enable or encourage opioid use (Gatewood et al, 2016; Smith et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…However, barriers to widespread access remain, and some people who use opioids still do not carry the medication, even if they were trained and given naloxone at no cost. In a recent national survey of attitudes toward naloxone among the general population, half of the respondents endorsed that "naloxone is only necessary for people who abuse opioids," and 51% of respondents endorsed that "having naloxone available enables more drug use among people who abuse opioids" [28]. These contested beliefs about the place and role of naloxone-who should have it and the behavioral impacts of possession and use-permeate across social networks of both people who use opioids and people who do not use drugs (or do not identify as people who use drugs) [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In general, expert opinion suggests that naloxone is only prescribed for those dependent on or addicted to opioids, which may deter patients from picking up naloxone prescriptions [ 28 ]. Other individuals may be concerned with judgement in inquiring about naloxone products in community pharmacies, or such that they would be labeled as addicts by law enforcement if found carrying it.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 study on public perceptions of naloxone use found that 61% of survey respondents had never heard of naloxone or were unaware that a medication existed to treat opioid overdose. Of respondents that self-reported current or past opioid use, over half felt they were not at risk of overdose [ 28 ]. Contrary to these misconceptions, the range of patients that may benefit from a naloxone prescription includes any individual using opioids, especially at higher doses, those who use opioids in combination with other sedating medications such as benzodiazepines, and those taking opioids who suffer from a chronic medical condition such as the human immunodeficiency virus, liver or lung disease, in addition to those who are opioid-dependent or people who inject opioids [ 31 ].…”
Section: Discussionmentioning
confidence: 99%